2019
DOI: 10.1155/2019/8676490
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Acupuncture in Treating Essential Hypertension: A Narrative Review

Abstract: Essential hypertension has a high incidence worldwide, and patients with essential hypertension endure a lifetime of medication, leading to a heavy economic burden on the patient’s family and causing serious impacts on the patient’s quality of life. Much evidence has demonstrated that acupuncture as an adjunctive therapy can lower blood pressure in patients with hypertension, but the mechanism of its action is unclear. This article reviews the research from 2000 to 2018 regarding the mechanism of acupuncture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 98 publications
0
25
0
2
Order By: Relevance
“…Therefore, it's hard to say which of these two aspects (the flora and the host) is the direct target of acupuncture. A recent review [ 69 ] summarized the mechanism of acupuncture in treating hypertension and found that renin–angiotensin–aldosterone system (RAAS), vascular endothelium, oxidative stress response, neuroendocrine system are all involved in the antihypertensive mechanisms of acupuncture while these mechanisms themselves are influenced by gut microbiota. In addition, previous studies showed EA could stimulate more SCFAs and improve the digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it's hard to say which of these two aspects (the flora and the host) is the direct target of acupuncture. A recent review [ 69 ] summarized the mechanism of acupuncture in treating hypertension and found that renin–angiotensin–aldosterone system (RAAS), vascular endothelium, oxidative stress response, neuroendocrine system are all involved in the antihypertensive mechanisms of acupuncture while these mechanisms themselves are influenced by gut microbiota. In addition, previous studies showed EA could stimulate more SCFAs and improve the digestion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that induction of 2-AG release in endothelium occurs in parallel to nitric oxide (NO) and involves activation of cholinergic receptors 88 . Nitric oxide, the most effective endothelium derived relaxing factor (EDRF), and endothelial derived hyperpolarizing factor (EDHF) 89 have a close functional relationship with ET-1 in regulating the endothelial-dependent capillary and microvascular responses in the brain 90 .…”
Section: Ecb In Neuroinflammationmentioning
confidence: 99%
“…Network pharmacology is widely used in drug discovery, mechanism research and target prediction, especially in TCM [ 5 , 78 ]. Relevant studies have recently proved that acupuncture involves multiple systems of the human body and has multi-target therapeutic effects, therefore, it is urgent to introduce novel research ideas into the research of the potential mechanisms of acupuncture [ 41 ]. In this study, we aimed to reveal the molecular mechanisms of acupuncture against COVID-19 through bioinformatics, network topology and network pharmacology approach, in order to further deepen the current understanding of the therapeutic nature of acupuncture on COVID-19.…”
Section: Introductionmentioning
confidence: 99%